An insight into sensitive detection of metal ions using a novel cobalt MOF: single crystal, photoluminescence, and theoretical studies. Issue 30 (13th July 2022) - Rana, Love Karan; Kaur, Prabhjyot; Maris, Thierry; Duong, Adam
Abstract : Sensitive detection of various metal ions is achieved using Co-MOF. Factors imparting sensing potential to Co-MOF and the structure/application (sensitive detection) relationship are discussed in the realm of 'crystal engineering'. Abstract : In this work, sensitive detection of various metal ions and anions using cobalt metal–organic frameworks has been studied. Furthermore, various sensor–analyte interactions that prompt changes in the fluorescence emission have been investigated and discussed in the realm of "crystal engineering". In this pursuit, three novel mixed ligand coordination compounds with the molecular formula {[Co3 (L1 )(μ-BDC )(BDC )2 (L1 )·(DMF)2 ]·DMF} n (1 ), {[Zn8 (μ2 -BTB )3 (BTB )(O )2 (L1 )(DMF)2 ]·4DMF} n (2 ) and {[Ni(L1 )(BDC )(EtOH/DMF)2 ]·EtOH} n (3 ) have been synthesized using a new naphthalene dicarboxamide ligand L1 ( N 2, N 6 -bis(pyridin-3-ylmethyl)naphthalene-2, 6-dicarboxamide) and two carboxylic acid-based ligands, viz. H 2 BDC (1, 4-benzene dicarboxylic acid) and H 3 BTB (1, 3, 5-tris(4-carboxyphenyl) benzene). Among these, 1 and 2 have solvent-accessible voids in the crystal structure but a single and stable fluorescence signal is observed only in the case of 1 and therefore it has been utilized for sensing studies. Various metal cations have been used in fluorescence titrations to test the sensing ability of 1, which is also referred to as Co-MOF in the following discussion. It was found that 1 is highly responsive to Fe +3, Ru +3, Pd +2, and Hg +2 ions and moderately responsive to Pb +2, Cd +2, Ni +2, Co +2, and Fe +2 ions. Interestingly, 1 gave no response upon the addition of Zn +2, Mn +2, Be +2 and all alkaline earth metal ions. Fluorescence experiments were also performed using different salts of Fe(iii ) and Cu(ii ) ions with different counterions. Distinct trends in the decrease in fluorescence intensity of 1 on varying the counter anions prompted us to perform anion sensing experiments. Addition of BF4 −, I −, NO3 −, and (SO4 ) −2 ions have caused a slight decrease in the fluorescence intensity of 1, while no response was observed towards ClO4 −, Br −, and SCN − ions. The potential mechanism of sensitive detection was proposed with the aid of DFT calculations performed on a model Co(ii ) complex, which illustrates that the excited state has a dominant contribution from naphthalene and carbonyl moieties and that the electron transfer can occur only if the analyte ions interact with either of the moieties or both. SCXRD reveals that compound 3 is a 3D coordination polymer with no solvent-accessible voids. Various characterization techniques, viz. NMR, SCXRD, PXRD, IR, TGA, and photoluminescence, were used to determine the structure and properties of L1 and 1–3 .